Analysis and selection of methods for customizing SAAS solutions built using Cloud-Native technologies - Romankiv, Nazarii; Sytnikov, Dmytro (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2023)
The subject of the study is the methods of customization of SaaS solutions. The purpose of the article is to determine a holistic strategy for customizing SaaS solutions developed using cloud-native technologies. Objectives: to analyze modern approaches to the architecture of SaaS applications; to identify the main methods of customization for modern SaaS applications; to investigate and establish a method for customizing the interface of SaaS applications; based on the study, to determine a comprehensive strategy for customizing SaaS applications. The following methods are implemented: analysis and synthesis - to study the technologies that are used to build SaaS applications; abstraction and generalization - to determine the overall architecture of the SaaS application; synthesis of web technologies - to select methods of customization of SaaS applications and build an algorithm for selecting a customization method. Results achieved: the modern architecture of SaaS applications is studied; methods of customization of SaaS applications are selected, and a holistic strategy for customization of SaaS applications is defined; a method for modifying the interface of SaaS applications is determined, which allows customization of the web interface of a SaaS application regardless of the specific front-end framework. Conclusions: modern architecture of SaaS applications is complex and based on microservice architecture, multi-tenant approach, cloud technologies and web browser; methods of customization of SaaS applications should be developed independently of certain technology stacks to meet the customization needs of most or all users of SaaS applications; the API-first approach is fundamental in building a customized SaaS, as it is the basis for creating any automation or related business logic; webhooks are the best option for implementing subscriptions to events occurring in a SaaS application, regardless of the technology stack; a defined strategy for customizing SaaS applications allows customization regardless of a particular technology stack and, in addition to implementing business logic, also covers interface modifications.